Awareness, perception and attitude of Malaysian consumers towards cosmetic products - Ab. Hadi, Hazrina; Awadh, Ammar Ihsan Jawad; Md. Jaffri, Juliana; Jamshed, Shazia Qasim (2015)
The cosmetic industry is growing rapidly, and cosmetic products are becoming an essential part of our daily lives. Moreover, increased usage of cosmetic products has caused a growing concern about the safety of these products, and yet little is known about cosmetics from the consumers’ perspective. Hence, this study’s aims are to explore consumers’ perspective towards cosmetic products and to develop a valid and reliable tool for assessing consumers’ awareness, perceptions and attitudes towards cosmetic products. Qualitative and quatitative method were adopted in this study and it is carreid out at public places in Kuantan,Pahang. This study was iniciated with an in-depth face-to-face interviews. An interview guide was developed with a set of twelve semi-structured questions. Purposive sampling was used to recruit participants in which the saturation point was achieved at the 28th interview, and two more interviews were conducted for confirmation of the themes. Unsatisfactory awareness related to cosmetic products in Malaysia was noted among the participants in this study. Although, at the time of the study, they were using conventional cosmetic products, the participants in this study showed a positive perception and attitude towards natural cosmetic products. However, the price and accessibility of natural cosmetic products may influence their purchase of cosmetic products. Subsequently, a questionnaire was developed in the English language based on information collected from the interviews session, a literature search, and consultations with experts. Next, the questionnaire was subjected to translation, validation and test-retest reliability A final version of the questionnaire was piloted among 66 consumers via convenient sampling. The results achieved via the Bahasa Malaysia questionnaire indicate that the developed and translated questionnaire can be used as a valid and reliable tool for assessing consumers’ awareness, perceptions and attitudes towards cosmetic products in Malaysia in future studies.